2022
DOI: 10.5551/jat.63030
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Kidney Function and Subclinical Atherosclerosis Progression Evaluated by Coronary Artery Calcification

Abstract: The roles of urinary albumin, eGFRcystatin (eGFRcys), and eGFRcreatinine (eGFRcre) in the progression of coronary artery calcification (CAC) remain unclear. Therefore, the present study investigated the relationship between kidney function and CAC progression.Methods: A total of 760 Japanese men aged 40-79 years were enrolled in this population-based study. Kidney function was measured using eGFRcre, eGFRcys, and the urine albumin-to-creatinine ratio. CAC scores were calculated using the Agatston method. CAC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…For renal biomarkers, our results were consistent with previous studies that demonstrated that CysC was associated with increased arterial stiffness 42 and can be an independent predictor of arterial stiffness in patients with type 2 diabetes mellitus 43 . Similar to previous findings, albuminuria was strongly related to endothelial dysfunction in the early phase of atherosclerosis; this relationship was enhanced in subjects with diabetes, 44 which by itself may predict subclinical atherosclerosis 45 . Existing literature also shows that longitudinal decline in renal function (creatinine and eGFR) is associated with higher levels of PWV 46 .…”
Section: Discussionsupporting
confidence: 84%
“…For renal biomarkers, our results were consistent with previous studies that demonstrated that CysC was associated with increased arterial stiffness 42 and can be an independent predictor of arterial stiffness in patients with type 2 diabetes mellitus 43 . Similar to previous findings, albuminuria was strongly related to endothelial dysfunction in the early phase of atherosclerosis; this relationship was enhanced in subjects with diabetes, 44 which by itself may predict subclinical atherosclerosis 45 . Existing literature also shows that longitudinal decline in renal function (creatinine and eGFR) is associated with higher levels of PWV 46 .…”
Section: Discussionsupporting
confidence: 84%
“…Hemodialysis is a well-known predictor for worse clinical outcomes after PCI, which was in line with the results of the current study. There is a significant association between kidney function and coronary artery calcification 29) . Moreover, Lee et al reported that hemodialysis is the independent predictor of CN 15) .…”
Section: Worse Clinical Outcomes Of Cnmentioning
confidence: 99%
“…In recent years, GFR and renal injury assessed by CysC have received increasing attention 24 , 25 . Studies have reported that eGFRcys is associated with tumors, subclinical atherosclerosis and coronary artery calcification 26 , 27 . However, few studies have focused on changes in eGFRcys after stroke and its association with stroke prognosis.…”
Section: Discussionmentioning
confidence: 99%